2011
DOI: 10.1038/ismej.2011.135
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability overwhelms seasonal patterns in bacterioplankton communities across a river to ocean gradient

Abstract: Few studies of microbial biogeography address variability across both multiple habitats and multiple seasons. Here we examine the spatial and temporal variability of bacterioplankton community composition of the Columbia River coastal margin using 16S amplicon pyrosequencing of 300 water samples collected in 2007 and 2008. Communities separated into seven groups (ANOSIM, Po0.001): river, estuary, plume, epipelagic, mesopelagic, shelf bottom (deptho350 m) and slope bottom (depth4850 m). The ordination of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
223
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 235 publications
(255 citation statements)
references
References 44 publications
20
223
2
1
Order By: Relevance
“…Hence, even if DNA-based BC composition is individually not significantly correlated with salinity (Supplementary Table S5), the canonical correlation to DOM molecular composition identifies the connection to terrestrial influence as an important driver of the North Sea. The presence of a general salinity gradient mirrored in the BC composition has been reported previously, for example, by Bouvier and del Giorgio (2002) and Fortunato et al (2012), who established salinity as the main driver of BC structure along a pronounced salinity gradient from river to ocean. In accordance to their findings, we hypothesize that the DOM compounds and the total BC that reach the North Sea undergo mixing and transformation processes from the coast toward the Atlantic on similar timescales of several months and thus retain the intermediate history of the water masses, the 'riverine legacy'.…”
Section: Identifying the Key Factors-bcmentioning
confidence: 85%
“…Hence, even if DNA-based BC composition is individually not significantly correlated with salinity (Supplementary Table S5), the canonical correlation to DOM molecular composition identifies the connection to terrestrial influence as an important driver of the North Sea. The presence of a general salinity gradient mirrored in the BC composition has been reported previously, for example, by Bouvier and del Giorgio (2002) and Fortunato et al (2012), who established salinity as the main driver of BC structure along a pronounced salinity gradient from river to ocean. In accordance to their findings, we hypothesize that the DOM compounds and the total BC that reach the North Sea undergo mixing and transformation processes from the coast toward the Atlantic on similar timescales of several months and thus retain the intermediate history of the water masses, the 'riverine legacy'.…”
Section: Identifying the Key Factors-bcmentioning
confidence: 85%
“…DNA samples (1-6 l per sample) were collected from 10 l Niskin bottles, preserved and extracted as described previously (Fortunato and Crump, 2011), and PCR-amplified for amplicon pyrosequencing using primers targeting bacterial 16S rRNA genes (Hamady et al, 2008) as described previously (Fortunato et al, 2012). Pyrosequencing was completed in two runs at Engencore at the University of South Carolina (http:// engencore.sc.edu/).…”
Section: Methodsmentioning
confidence: 99%
“…An earlier study of 300 water samples collected in 2007 and 2008 showed bacterioplankton communities of the Columbia River coastal margin separated into seven environments: river, estuary, plume, epipelagic, mesopelagic, shelf bottom and slope bottom (Fortunato et al, 2012). Here we expand on this work and focus on population-level analyses to determine the key taxa in each environment and describe how the relative abundance of these taxa shifts with changing environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations